1990
DOI: 10.1007/bf01184503
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate, nitrite, and N-nitroso compounds in Finnish foods and the estimation of the dietary intakes

Abstract: An estimate of the dietary intakes of nitrite, nitrate and N-nitroso compounds is presented, based on the analytical data supplied by the Finnish Food Quality Control. Figures on the food consumption of the Finnish population, taken from a national dietary survey, and food consumption of 1768 children and adolescents over a 48-h recall period were used. The mean daily dietary nitrate intakes were estimated to be about 55 mg for the total population and for children and adolescents. The mean nitrite intakes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…Taking into account only potatoes, vegetables and fruits and some drinks, results are 376 similar to a Finnish study that reported an intake of 55mg/day (or 0.92mg/kg bw/day) 377 (Penttilä et al 1990) . Penttilä et al (Penttilä et al, 1990) probably underestimated the intake 378 of nitrate by drinks. Calculating back the intake of coffee and soft drinks is on average 379 50ml/day.…”
supporting
confidence: 72%
“…Taking into account only potatoes, vegetables and fruits and some drinks, results are 376 similar to a Finnish study that reported an intake of 55mg/day (or 0.92mg/kg bw/day) 377 (Penttilä et al 1990) . Penttilä et al (Penttilä et al, 1990) probably underestimated the intake 378 of nitrate by drinks. Calculating back the intake of coffee and soft drinks is on average 379 50ml/day.…”
supporting
confidence: 72%
“…Studies on daily dietary intake of nitrate in the human body have been conducted in different European Union countries like Slovenia (Susin, 2006), Estonia (Tamme, 2006), Denmark (Petersen, 1999), Spain (Pardo-Marín, 2010; Quijano, 2016), Poland (Mitek, 2013;Szymczak, 1999), Italy (Lucarini, 2012), Belgium (Temme, 2011), Finland (Penttilä, 1990), and France (Menard,2008), as well as in some other countries in the world (Santamaria, 1999), like Korea , China (Zhong, 2002), Honk Kong (Chung, 2011), the USA (Nuñez de González, 2015) In all these studies, daily intakes of nitrate in the body were determined based on the results of research into the presence of nitrate in various types of food.…”
Section: Discussionmentioning
confidence: 99%
“…In a Finnish study, conducted between 1966 and 1972, mean intake of nitrite was 5.3 mg day 21 , provided nearly exclusively by cured meats and PM 5,36 . However, another report from Finland calculated an average daily intake of 1.88 mg 33 . In the UK, a daily nitrite intake of 2.4-4.2 mg has been reported 37 , which is higher than estimated for the British EPIC cohort.…”
Section: Table 2bmentioning
confidence: 99%